Durable response to the combination of pembrolizumab and nab-paclitaxel in a metastatic extrahepatic cholangiocarcinoma: A case report and literature review - Tan, Sirui; Yu, Jing; Huang, Qiyue; Zhou, Nan; Xiong, Xianze; Gou, Hongfeng (Frontiers in Pharmacology, 2022)
Background: Cholangiocarcinoma (CCA) is a highly aggressive malignant tumor with poor overall survival. Although the first-line standard chemotherapy (gemcitabine plus cisplatin) combined with immunotherapy has yielded positive results with survival prolongation, the efficacy remains unsatisfactory, and new treatment modalities need to be explored. Case presentation: We report the case of a patient with metastatic extrahepatic CCA who achieved a durable response and good tolerance to the combination treatment of pembrolizumab and nab-paclitaxel following progression on gemcitabine plus capecitabine chemotherapy. The tumor samples of the patient revealed low TMB, MSS, negative PD-L1 expression, and negative CD8+ TIL expression. This patient was treated with 3 cycles of pembrolizumab plus nab-paclitaxel and cisplatin, followed by 5 cycles of pembrolizumab plus nab-paclitaxel. Finally, 10 cycles of pembrolizumab monotherapy were administered. The patient survived for over 27 months after the initiation of combined therapy and was still in continuous remission at the last follow-up. Conclusion: As far as we know, this is the first report that pembrolizumab plus nab-paclitaxel successfully treated a patient with advanced CCA. This combination therapy might be a potential treatment option for patients with cholangiocarcinoma, and further clinical trials are needed to explore the outcomes.